(La0.5-xPrBa0.5)(Mn0.5Ti0.5)O3 Perovskite: microstructural and electrical properties - Shaari, Abdul Halim; Wan Yusoff, Wan Mohamad Daud; Alias, Nor Hayati; Mahmood, Che Seman (Malaysian Solid State Science and Technology Society, 2008)
A new perovskite of titano-manganite based (La0.5-xPrxBa0.5)(Mn0.5Ti0.5)O3 has been prepared by ceramic solid-state technique at sintering temperature 1300 °C. The concentration of Pr, x, in molar proportion in A site has been varied as x = 0.0, 0.1, 0.2, 0.3 and 0.4. Analysis has been carried out to determine microstructure and electrical properties of the synthesized material. It is found that at sintering temperature 1300 °C, only sample with x=0.1 produce a better diffused condition with low dielectric loss.